Analysis of the computing power of the interlineational finite element method of solution of the non-stationary heat conduction problem - Sergienko, I. V.; Lytvyn, O. M.; Lobanova, L. S.; Zaluzhna, G. V. (Reports of the National Academy of Sciences of Ukraine, 2014)
Some aspects of a numerical implementation of the interlineational finite element method solution of the non-stationary heat conduction problem for planar domains with complex shapes are considered.It is proposed to test this method, by using exact solutions, for which the method of construction is proposed by the authors. The interlineational finite element method allows us to reduce the non-stationary heat conduction problem to the Cauchy problem for a system of ordinary differential equations of lower order than in the classical finite element method.